A Ferrocenyl‐Benzo‐Fused Imidazolylidene Complex of Ruthenium as Redox‐Switchable Catalyst for the Transfer Hydrogenation of Ketones and Imines. Issue 24 (1st December 2016) - Ibáñez, Susana; Poyatos, Macarena; Peris, Eduardo
Abstract: A ferrocenyl‐benzo‐fused imidazolylidene complex of Ru II was prepared and fully characterized. In the presence of acetylferrocenium tetrafluoroborate this complex can be oxidized to generate a complex with a cationic ligand. The neutral complex can be recovered by reducing the oxidized cationic compound with cobaltocene. The activity of the neutral and oxidized complexes was tested in the transfer hydrogenation of ketones and imines, using isopropyl alcohol as the hydrogen source. The neutral complex is very active in the reduction of all tested substrates, whereas the oxidized species shows low activity in the reduction of ketones. The rate of the reduction of hexaphenone could be modulated by addition of subsequent amounts of oxidant and reductant. The addition of acetylferrocenium tetrafluoroborate caused a decrease in the catalytic activity, whereas the addition of cobaltocene restored the activity. The catalytic activity shown by both catalysts in the reduction of N ‐benzylideneaniline was similar. Abstract : Good or bad : A ferrocenyl‐benzo‐fused‐imidazolylidene complex of Ru II is used as a redox‐switchable catalyst in the transfer hydrogenation of ketones and imines. The activity of the catalyst significantly decreases in the presence of an oxidant.